An efficient approach to the evaluation of wind effects on structures based on recorded pressure fields. (1st October 2016) - Patruno, L.; Ricci, M.; de Miranda, S.; Ubertini, F.
Highlights: An efficient approach to the calculation of the response to wind loading is proposed. Static corrections are introduced in order to take into account the effects of high-frequency modes. A new class of pressure modes is introduced, which represents an efficient alternative to influence coefficients. The characterization of the structural response to wind loading is easily obtained. Abstract: A well known peculiarity of the structural response to wind loading is that static, quasi-static and resonant effects are present, in general, without a clearly dominant contribution. In such conditions, the calculation of wind effects would require to consider a large number of modes due to the relevant contribution of high frequency ones. In the present paper, in order to alleviate inaccuracies in the evaluation of static and quasi-static effects, induced by the truncation of the modal base, an efficient approach to the evaluation of static and quasi-static corrections is developed. To this purpose, a new class of pressure modes, called Proper Skin Modes (PSMs), is introduced and the corrections are evaluated based on the structural response to such modes, statically applied. PSMs can be seen as a novel modal version of traditionally adopted influence coefficients and naturally arise from the adopted pressure interpolation technique. The obtained approach is compact and efficient leading to a reduced data exchange between structural and wind engineers and to an optimal organization of the software used to perform the analyses. The proposed procedure is tested on a low-rise and a high-rise building showing very good performances.